Beneficial role of gut microbes in maintenance of pace-of-life traits in Phrynocephalus vlangalii - Bing, Zhaohui; Niu, Chenkai; Yang, Cui; Qi, Yue; Zhao, Yangyang; Cao, Shuhui; Zhao, Wei (Frontiers in Microbiomes, 2022)
The pace of life syndrome theory suggests that species, populations, and individuals are positioned along a slow–fast pace of life continuum. However, whether and how individuals maintain a fast pace of life in a slow pace of life population remains unknown. In this study, the boldness and foraging behavior of Phrynocephalus vlangalii from Maduo (4250 m, above sea level), a typical slow-paced population, were screened frequently. Both behaviors of P. vlangalii were significantly recurrent and linked with one another. Based on boldness and foraging behavior, the lizards were divided into positive and shy groups, and their gut microbial diversity were studied using 16S rRNA gene sequencing. No significant difference in α diversity was observed; however, a significant difference existed in the β diversity of gut microbes between the two groups. Principal coordinate analysis indicated that the gut microbes in the two groups were distinct. Linear discriminant analysis effect size determined that the shy group contained a more significant proportion of Rikenellaceae and Clostridia. In contrast, the positive group had a higher proportion of Verrucomicrobiota, Verrucomicrobiae, and Akkermansiaceae. Kyoto encyclopedia of genes and genomes pathway analysis revealed that biodegradation and metabolism, including lipid metabolism and glycan biosynthesis, were higher in the positive group; on the contrary, nucleotide metabolism and enzyme families were significantly higher in the shy group. The results showed that positive lizards had more beneficial intestinal microflora for lipid and glucose metabolism to satisfy their high metabolic energy demand; while shy lizards had more beneficial intestinal microflora for maintaining an elevated fasting blood glucose, a long lifespan, and a more stable metabolism to sustain their slow pace of life. In this study, we validated a strong relationship between the individual's pace of life traits and intestinal microbiota in P. vlangalii. Further, we demonstrated that gut microorganisms are essential in sustaining the energy-intensive personality traits at high altitudes.